1988
DOI: 10.1128/aem.54.5.1131-1137.1988
|View full text |Cite
|
Sign up to set email alerts
|

Production, Distribution, and Kinetic Properties of Inulinase in Continuous Cultures of Kluyveromyces marxianus CBS 6556

Abstract: From a screening of several Kluyveromyces strains, the yeast Kluyveromyces marxianus CBS 6556 was selected for a study of the parameters relevant to the commercial production of inulinase (EC 3.2.1.7). This yeast exhibited superior properties with respect to growth at elevated temperatures (40 to 45°C), substrate specificity, and inulinase production. In sucrose-limited chemostat cultures growing on mineral medium, the amount of enzyme decreased from 52 U mg of cell dry weight-' at D = 0.1 h-l to 2 U mg of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
14

Year Published

1990
1990
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 25 publications
2
45
1
14
Order By: Relevance
“…Under glucose-limited growth (derepressing conditions), considerable amounts of the enzyme were detected (Table 2). This derepressing effect during continuous cultivation at low growth rates has also been reported for the extracellular enzyme inulinase (Rouwenhorst et al, 1988).…”
Section: Regulation Of Growth On Maltosesupporting
confidence: 71%
“…Under glucose-limited growth (derepressing conditions), considerable amounts of the enzyme were detected (Table 2). This derepressing effect during continuous cultivation at low growth rates has also been reported for the extracellular enzyme inulinase (Rouwenhorst et al, 1988).…”
Section: Regulation Of Growth On Maltosesupporting
confidence: 71%
“…In spite of this, these studies have shown that K. marxianus is very versatile and could be economically explored for a very wide range of applications. Examples include the production of ethanol (Singh et al, 1998;Kourkoutas et al, 2002), cell protein (Kim et al, 1998;Grba et al, 2002;Schultz et al, 2006), bioingredients (Belem & Lee, 1998), enzymes, such as inulinase (Rouwenhorst et al, 1988;Hensing et al, 1994Hensing et al, , 1995Passador-Gurgel et al, 1996), lactase (Rech et al, 1999;Martins et al, 2002), pectinase (Cruz-Guerrero et al, 1999), lipase (Deive et al, 2003), as well as aroma compounds (Wittmann et al, 2002;Etschmann et al, 2004), and its use as baker's yeast (Caballero et al, 1995) and as an anticholesterolemic agent (Yoshida et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of K. marxianus has been reported, in the last years, in dairy products [1,2], in fermented drinks [3,4], and in aged cheeses [5,6], in which it seems to play an important role in the development of the functional and sensorial features of the end products. Besides, it has been used in dairy products treatment to eliminate lactose [7], in apple juice to eliminate pectic residues [8], in the production of inulinase [9], and in biodegradation of xenobiotic agents [10]. The biochemistry and the genetics of the proteolytic system of K. marxianus have not been studied, despite its potential industrial relevance.…”
Section: Introductionmentioning
confidence: 99%